Optical Lectin Based Biosensor as Tool for Bacteria Identification - Masarova, Jana; Dey, Estera; Danielsson, Bengt (Polish Journal of Microbiology, 2004)
Biosensor techniques are based on biospecific interaction between the biological parts of biosensor with the analyte. In biosensor construction, antibodies are usually used for the detection of analytes such as microorganism, because of very strong and highly specific interaction. The disadvantages of this assay are a long time needed for antibody isolation and purification as well as difficult regeneration of biosensor chip. The use of lectins instead of antibodies could solve these problems because a several hundred lectins are commercially available and their stability in standard buffers is better compared to monoclonal antibodies. While antibody can only be used to detect that antigen it was designed for, lectin as low affinity molecule may bind several different pathogens. Using the discriminative effect of an artificial neural network the application of a lectin array will compensate for the lower specificity. Microbial surfaces bear many of the sugar residues capable of interacting with lectins. The ability of lectins to react with microbial glycoconjugates means that it is possible to employ them as probes and sorbents for whole cells, mutants and numerous cellular constituents and metabolites, and it makes them useful tools for identification or typing of bacteria. Lectins are attractive reagents for the clinical diagnostic laboratory because of their diverse specificity, commercial availability, a wide range of molecular weights, and their stability in standard buffers. The construction of lectin biosensor could be an advantage method for detection of pathogenic bacteria.